PREDICTION OF THE RISK OF DEVELOPING SECONDARY EMPTY SELLA SYNDROME - Shagazatova B.Kh., Artikova D.M. (Central Asian Journal of Medicine, 2025)
A prognostic assessment of risk factors for the development of secondary empty sella syndrome with the formation of risk groups was performed using 51 individuals as an example. Risk factors for the development of secondary ESS syndrome include a history of treatment of pituitary micro- and macroadenomas with dopamine agonists, the number of pregnancies up to 3, then in descending order normal body weight, age of patients from 30 to 40 years, men, and headaches.